The Role Played by the Family in Shaping Early and Middle Adolescent Civic Responsibility. (February 2014) - Lenzi, Michela; Vieno, Alessio; Santinello, Massimo; Nation, Maury; Voight, Adam
Adopting a multi-informant methodology, the current study examines the relative influence of multiple parental characteristics (civic responsibility, encouragement of civic action, parent-youth closeness) on adolescents' civic responsibility (local and global). The participants were 384 early and middle adolescents (47.9% male), randomly selected from an Italian city (mean age = 13.6; SD = 1.63), and one parent for each adolescent. The results show a positive association between the parents' local civic responsibility and the adolescents' responsibility toward the local community, and between the parents' global civic responsibility and the adolescents' responsibility toward societal issues. Moreover, parental encouragement of civic action and parent-youth closeness were positively associated with the adolescents' civic responsibility. Finally, an interaction between the parents' local civic responsibility and parent-child closeness was found in which parents' civic responsibility had stronger influence on youth civic responsibility when the parent-child relationship was characterized by medium or high levels of closeness.